Perceived discrimination and psychological crisis among Chinese college students: a chain-mediation model of sense of life meaning and self-esteem - Xu, Lijuan; Li, Li (Frontiers in Psychology, 2025)
BackgroundPerceived discrimination constitutes an essential factor influencing the psychological crisis of college students. While prior research has examined the impact of discrimination on mental health in China, this study is the first to systematically investigate the chain mediating role of sense of life meaning and self-esteem in the relationship between perceived discrimination and psychological crisis. This approach not only enhances the theoretical framework of the relationship between discrimination and mental health but also offers a novel perspective for understanding discrimination-induced psychological crises in Chinese society.ObjectiveThe present study used a questionnaire survey to test whether perceived discrimination may be associated with psychological crisis in Chinese college students. The mediating roles of sense of life meaning and self-esteem were also examined.MethodsIn total, 514 college students were recruited to complete four scales, including the Perceived Discrimination Questionnaire, the Sense of Life Meaning Questionnaire, the Self-Esteem Scale, and the college student psychological crisis screening scale.ResultsThe findings are: (1) Perceived discrimination, sense of life meaning, and self-esteem have significant direct predictive effects on college students’ psychological crisis; and (2) sense of life meaning and self-esteem play a chain-mediating role in the relationship between perceived discrimination and psychological crisis of college students. The mediating effect includes two paths: perceived discrimination → self-esteem → psychological crisis (effect size: 0.130) and perceived discrimination → sense of life meaning → self-esteem → psychological crisis (effect size: 0.030).ConclusionThis research highlights that perceived discrimination can directly predict the psychological crisis of Chinese college students, and it can indirectly influence the level of psychological crisis of Chinese college students through the chain-mediating effect of sense of life meaning and self-esteem. The findings provide colleges and universities with valuable insights into the causes of students’ psychological crises, aiding in the adjustment of mental health education strategies and formulation of effective support systems for discriminated students. Additionally, this study offers a robust scientific foundation for policymakers to develop and promote anti-discrimination policies, and foster social harmony.